1996
DOI: 10.1177/1077559596001002005
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Child Interaction Therapy: An Intensive Dyadic Intervention for Physically Abusive Families

Abstract: A designated priority in the field of child maltreatment is the development of empirical approaches for treating abusive families. This article describes parent-child interaction therapy (PCIT), an intervention that has been shown to be effective for helping parents manage young children with severe behavioral problems. The potential application of this treatment program to the child maltreatment field is examined by (a) providing a social learning perspective to explain the development and stability of some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 60 publications
3
84
0
1
Order By: Relevance
“…It has also been documented to be effective in ameliorating those same problems among maltreated children (Borrego et al, 1999;Urquiza and McNeil, 1996). PCIT contains two phases, each of which is preceded by a didactic session.…”
Section: Parent-child Interaction Therapy (Pcit)mentioning
confidence: 98%
“…It has also been documented to be effective in ameliorating those same problems among maltreated children (Borrego et al, 1999;Urquiza and McNeil, 1996). PCIT contains two phases, each of which is preceded by a didactic session.…”
Section: Parent-child Interaction Therapy (Pcit)mentioning
confidence: 98%
“…PCIT has also been successfully adapted for services with a wide range of populations. Examples include children with developmental delays (Eyberg & Matarrazzo, 1980), separation anxiety disorder (Pincus, Choate, Eyberg, & Barlow, 2005), chronic illness (Bagner, Fernandez, & Eyberg, 2004), histories of physical abuse (Chaffin et al, 2004;Urquiza & McNeil, 1996), and histories of general maltreatment (Fricker-Elhai, Ruggiero, & Smith, 2005 Mexican American (McCabe, Yeh, Garland, Lau, & Chavez, 2005), Puerto Rican (Matos 22 et al, 2006), Chinese (Leung, Tsang, Heung, & Yiu, in press), Norwegian (Bjørseth & Wormdal, 2005), and Australian families (Nixon, Sweeney, Erickson, & Touyz, 2003;Phillips, Morgan, Cawthorne, & Barnett, 2008). showed significantly greater reductions in reported parenting stress and improvements in disciplinary practices when compared with the waitlist control group.…”
Section: Long-term Maintenance Of Pcitmentioning
confidence: 99%
“…The investigators indicated that their study participants typically experienced minor types of abuse, and noted the need for further evaluation of AF-CBT with children who experience severe physical abuse (Kolko, 1996). Parent-Child Interaction Therapy Parent-Child (PCIT) therapy was originally developed for children with externalizing behavior problems (Eyberg, 1988), but has now been suggested for physically abusive parents and their children (Urquiza & McNeil, 1996). PCIT is based on behavioral parenting principles and involves step-by-step live coaching of parent-child interactions.…”
Section: Violence Exposure Treatments Evaluating Other Child Outcomesmentioning
confidence: 99%
“…Treatments also aim to lessen coercive interactions by emphasizing more positive and supportive parenting techniques, sometimes through direct coaching during observed parentchild interactions (Urquiza & McNeil, 1996). Kolko (1996) worked with the entire family to promote identification and reduction of coercive behaviors and to replace them with constructive problem solving and positive communication skills.…”
Section: Parenting Interventionsmentioning
confidence: 99%